Semiclassical theory of mesoscopic quantum systems - Richter, Klaus, 1962- (Springer tracts in modern physics, 2000)
This book describes manifestations of classical dynamics and chaos in the quantum properties of mesoscopic systems. During the last two decades mesoscopic physics has evolved into a rapidly progressing and exciting interdisciplinary field of physics. The first part of the book deals with integrable and chaotic classical dynamics with particular emphasis on the semiclassical description of spectral correlations, thermodynamic properties and linear response functions. The main part shows applications to prominent observables in the mesoscopic context.